Central South Slavic Linguistic Taxonomies and the Language/Dialect Dichotomy: Rhetorical Strategies and Faulty Epistemologies - Maxwell Alexander; Vukotić Vuk; Klaver Susie (Comparative Southeast European Studies)
This article analyzes the epistemology of the language/dialect (L/D) dichotomy. The L/D dichotomy gives rise to disputes between “splitters”, who want to split the speech of a given region into more than one “language”, and “lumpers”, who view the region as speaking one “language” albeit with diverse “dialects”. While numerous linguists have declared the L/D dichotomy theoretically meaningless, thus taking an “agnostic” approach, linguists interested in a particular case study often take sides in lumper/splitter disputes. Such linguists, who the authors call “assertionists”, adopt a variety of rhetorical strategies to make their case. Taking as a case study assertionists writing about Central South Slavic, this article identifies three main strategies: the “avalanche of trivia”; the “appeal to imaginary evidence”; and the “denigration of the political”. Both lumpers and splitters adopt all three strategies to conceal the poor epistemological foundations of assertionism.